2018
DOI: 10.1155/2018/8308361
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Nutritional Properties and Sensory Evaluation of Bread Fortified with Natural Sources of Calcium

Abstract: By-products of oyster shell and egg shell are new candidates for use as calcium supplements. e e ect of the forti cation of bread with natural sources of calcium such as skim milk powder, egg shell powder, and oyster shell powder at levels of 10%, 2%, and 2%, respectively, on the rheological, nutritional, and sensory properties was determined. Compared to the control bread, breads forti ed with egg and oyster shells had a higher water absorption (%), dough development time, dough stability, mixing time, heat o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
4
21
0
1
Order By: Relevance
“…Growing interest is now focused to ES powder because it can be used as a mineral source for fortification of different food products, e.g., yoghurt [13], biscuits [14], chocolate cakes [15], bread [16][17][18]. Based on this information, this study contributes to the valorisation of food waste (ES) to obtain a new product: white bread enriched in Ca as a natural source.…”
Section: Introductionmentioning
confidence: 99%
“…Growing interest is now focused to ES powder because it can be used as a mineral source for fortification of different food products, e.g., yoghurt [13], biscuits [14], chocolate cakes [15], bread [16][17][18]. Based on this information, this study contributes to the valorisation of food waste (ES) to obtain a new product: white bread enriched in Ca as a natural source.…”
Section: Introductionmentioning
confidence: 99%
“…Man et al [13] reported that the addition of 30% chickpea flour increased the ash content of wheat flour by four times. An increase was observed in the same elements during bread fortification with different dairy products (milk powder, whey protein concentrate powder, and buttermilk powder) with significantly higher levels than wheat bread [41,42].…”
Section: Mineral Compositionmentioning
confidence: 95%
“…In addition, the eggshell and oyster bread had significantly higher levels of calcium, iron, zinc, and phosphorus than the control. The fortification of bread with natural sources of calcium, such as skimmed milk powder and waste products, like oyster shell and eggshell powders, was demonstrated to improve the rheological characteristics of dough and the quality and nutritional properties compared to the control bread [ 89 ]. Although some studies investigated the high value of calcium from seafood by-products as food supplement, it must be considered that solubilization and ionization processes are necessary for its real adsorption.…”
Section: Mineral Saltsmentioning
confidence: 99%